2017
DOI: 10.1111/ap.12265
|View full text |Cite
|
Sign up to set email alerts
|

Competency‐based Clinical Supervision: Status, Opportunities, Tensions, and the Future

Abstract: Although competency-based clinical supervision has been adopted in many international clinical training settings, acceptance has been variable with scholarly opinion outpacing actual practice. The transtheoretical molecular model, as articulated by Gonsalvez and Calvert (2014), offers a structure for advancing competency-based supervision and an important contribution, providing for definition of content and processes implicit in supervision practice. Barriers to implementation of competency-based supervision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 61 publications
(60 reference statements)
2
44
0
2
Order By: Relevance
“…Video feedback methods used during clinical training are generally thought to assist supervisors in providing accurate feedback on strengths and weaknesses, which may better inform trainee self-reflection and their ability to self-assess their competence (Falender & Shafranske, 2017;Sutton, Townend, & Wright, 2007). In-vivo and delayed videobased reviews, as well as simulated role plays are common examples of observation-based supervisory instruments, which have been heralded as necessary for instilling reflective practice and improving self-assessment (Gonsalvez, Brockman, & Hill, 2016;Kaslow, Celano, & Stanton, 2009).…”
Section: Effects Of Supervisory Methods On Accuracy Of Self-assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Video feedback methods used during clinical training are generally thought to assist supervisors in providing accurate feedback on strengths and weaknesses, which may better inform trainee self-reflection and their ability to self-assess their competence (Falender & Shafranske, 2017;Sutton, Townend, & Wright, 2007). In-vivo and delayed videobased reviews, as well as simulated role plays are common examples of observation-based supervisory instruments, which have been heralded as necessary for instilling reflective practice and improving self-assessment (Gonsalvez, Brockman, & Hill, 2016;Kaslow, Celano, & Stanton, 2009).…”
Section: Effects Of Supervisory Methods On Accuracy Of Self-assessmentmentioning
confidence: 99%
“…Although training programs purport to implement various activities to promote the development of trainees' reflective practice (Orchowski, Evangelista, & Probst, 2010), given the dearth of empirical research, it is unclear how effective most are (Cooper et al, 2015). A key aspect of training thought to facilitate accurate reflective self-assessment is the provision of observation informed supervision (Falender & Shafranske, 2017;Gonsalvez, Brockman, & Hill, 2016).…”
Section: Effects Of Reflective Practice Training On Accuracy Of Selmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, while the current review only concerns EBP competencies, the identified research gap raises concerns about potential neglect of other competencies, especially those recently highlighted by expert groups as warranting special attention (e.g., Falender & Shafranske, ). These competencies include but are not limited to diversity and multicultural competence, reflective practice, and ethical attitudes and behaviours.…”
Section: Discussionmentioning
confidence: 99%